2021
DOI: 10.21203/rs.3.rs-490573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cuticular hydrocarbon profile for queen recognition in the termite Reticulitermes speratus

Abstract: Chemical communication underlies the sophisticated colony organization of social insects. In these insects, cuticular hydrocarbons (CHCs) play central roles in nestmate, task, and caste recognition, which contribute to maintenance of the social and reproductive division of labor. Queen-specific CHCs reflect queen fertility status and function as a queen recognition pheromone, triggering aggregation responses around the queens. However, there are only a few studies about the royal recognition mechanism in termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Hence, it is likely that other compounds may be responsible for physical queen recognition. Recent observations in the genus Reticulitermes have shown that recognition of reproductives, accompanied by appropriate behavior, is mediated by king/queen-specific CHCs 29,30,45 . Therefore, in line with some predictions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is likely that other compounds may be responsible for physical queen recognition. Recent observations in the genus Reticulitermes have shown that recognition of reproductives, accompanied by appropriate behavior, is mediated by king/queen-specific CHCs 29,30,45 . Therefore, in line with some predictions (e.g.…”
Section: Discussionmentioning
confidence: 99%